Generalized -D-gap functions and error bounds for a class of equilibrium problems. Issue 14 (26th October 2017) - Ceng, Lu-Chuan; Sahu, D. R.; Wen, Ching-Feng; Wong, Ngai-Ching
Abstract: In this paper, we introduce and study the generalized - D -gap function for an equilibrium problem. We give sufficient conditions under which a critical point of the generalized - D -gap function is a solution of the equilibrium problem, and develop a descent scheme for locating these critical points. Using the generalized - D -gap function, we construct an error bound for the equilibrium problem. We support our approach with concrete examples.